2012
DOI: 10.1126/science.1224676
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Tracing Reveals Lgr5 + Stem Cell Activity in Mouse Intestinal Adenomas

Abstract: The concept that tumors are maintained by dedicated stem cells, the so-called cancer stem cell hypothesis, has attracted great interest but remains controversial. Studying mouse models, we provide direct, functional evidence for the presence of stem cell activity within primary intestinal adenomas, a precursor to intestinal cancer. By "lineage retracing" using the multicolor Cre-reporter R26R-Confetti, we demonstrate that the crypt stem cell marker Lgr5 (leucine-rich repeat-containing heterotrimeric guanine nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
809
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,010 publications
(849 citation statements)
references
References 29 publications
34
809
0
6
Order By: Relevance
“…In this case, the role of specific genes in the spontaneous generation of tumours can be examined using transgenic technology, as well as transplantation assays that can use syngeneic recipients of any age. More recently, lineage tracing has been exploited to add further strong evidence of CSCs in glioblastomas, intestinal adenomas and epidermal tumours developing de novo in mice and, in the case of the glioblastoma, their anticipated drug resistance was also demonstrated [61][62][63] . These findings highlight how mouse models of tumorigenesis may facilitate the future development of methods for interrogating CSCs in patient samples for clinical purposes.…”
Section: Csc Assays: Strengths and Caveatsmentioning
confidence: 99%
“…In this case, the role of specific genes in the spontaneous generation of tumours can be examined using transgenic technology, as well as transplantation assays that can use syngeneic recipients of any age. More recently, lineage tracing has been exploited to add further strong evidence of CSCs in glioblastomas, intestinal adenomas and epidermal tumours developing de novo in mice and, in the case of the glioblastoma, their anticipated drug resistance was also demonstrated [61][62][63] . These findings highlight how mouse models of tumorigenesis may facilitate the future development of methods for interrogating CSCs in patient samples for clinical purposes.…”
Section: Csc Assays: Strengths and Caveatsmentioning
confidence: 99%
“…In most cases, they are referred to as tumor-initiating cells (TICs). The existence of CSC population remains a controversial topic due to questions about the robustness of CSC markers (Magee et al, 2012), however, three independent studies successfully identified and tracked CSCs in brain, skin and intestinal tumors of mice Driessens et al, 2012;Schepers et al, 2012). These findings might provide further evidence to support that CSCs are the driving force of tumor development (Gilbertson and Graham, 2012).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Schepers et al used the intestinal adenoma (a premalignant precursor lesion; driver mutation is APC null mutation)-prone mouse model and Driessens et al used a benign papilloma mouse model to drive home an important point: tumours are maintained by dedicated cancer stem cells, and tumour growth is analogous to normal tissue renewal and architecture [56,57]. Schepers et al brought a loxP cassette containing four fluorescent labels in the background of adenoma-prone mouse which conditionally express Cre recombinase and in which intestinal stem cells are labelled with GFP.…”
Section: Controversy About the Existence Of Cancer Stem Cellsmentioning
confidence: 99%
“…Early after retracing, there was co-expression of new colour and GFP, indicating that colour change has tracked CSC. When this was followed for many days after retracing, progeny of newly coloured stem cells was seen to populate the adenoma with the architecture resembling normal intestinal growth, indicating that tumours are maintained by CSCs still retaining a semblance of the normal tissue architecture [56]. Similarly, Driessens et al labelled individual tumour cells, without labelling stem cells specifically, in the papillomas formed in the carcinogen followed by mitogen applied mice.…”
Section: Controversy About the Existence Of Cancer Stem Cellsmentioning
confidence: 99%